Teaching Reading Comprehension By Using Metacognitive Strategy: Read, Ask, Paraphrase (Rap) At Senior High School - Fatima Zahra; Fitrawati Fitrawati (Universitas Negeri Padang, 2017)
This paper describes the application one of the techniques in metacognitive strategy: Read, Ask and Paraphrase (RAP in the process of teaching reading comprehension at senior high school students. This strategy encourages students to improve attention and enthusiasm in learning English, especially in reading comprehension. RAP technique consists of 3 steps that is done in turn for each of the activities: reading, asking questions, and paraphrase. The first activity, Read, can help students to be more careful in reading. Then Questioning can assist students in determining the main idea and supporting details in each paragraph. And finally, in a paraphrasing will help students to remember information he had read so that it can be easier to understand the text reading. By using this strategy, the writer hopes that students can improve reading comprehension.